THE INFLUENCE OF SELF-EFFICACY AND LEARNING MOTIVATION OF HIGH SCHOOL STUDENTS ON THE UNDERSTANDING OF THE CONCEPTS OF WORK AND ENERGY - Fatonah, Uci; Wicaksana, Ervan Johan (EduFisika: Jurnal Pendidikan Fisika, 2023)
This research is the first to investigate the relationship between studentsâ€™ self-efficacy, learning motivation, and conceptual understanding of the concepts of work and energy. The research aims to explore how studentsâ€™ beliefs and attitudes affect their comprehension and application of physics concepts in various contexts. This quantitative descriptive study has 106 respondents from Senior High School 7 and 16 in the Bungo Regency. Data collection was conducted using validated questionnaires, interviews, and diagnostic tests. The results show that the average self-efficacy at Senior High School 7 and Senior High School 16 in the Bungo Regency is categorized as â€œvery good.â€ Student learning motivation at Senior High School 7 Bungo is classified as â€œfair,â€ while at Senior High School 16 Bungo, it is categorized as â€œgood.â€ Studentsâ€™ conceptual understanding at Senior High School 7 Bungo is classified as â€œfair,â€ while at Senior High School 16 Bungo, it is categorized as â€œgood.â€ The research also reveals an influence between studentsâ€™ self-efficacy and learning motivation on understanding the concepts of work and energy, with a contribution of 67%. The remaining 33% is influenced by other factors not examined in this study. The novelty of this research is that it introduces a new measure of conceptual understanding based on a diagnostic test that covers multiple aspects of work and energy, such as definition, calculation, conservation, and transformation. The research also provides empirical evidence of the positive impact of self-efficacy and motivation on conceptual understanding in physics learning.